The humbling - Roth, Philip 1933-2018 (Houghton Mifflin Harcourt, 2009)
What happens when all the ways that we convince ourselves of our solidity, all our life's performances--talent, love, sex, hope, energy, reputation--are stripped off? Simon Axler, one of the leading American stage actors of his generation, is about to find out. Now in his sixties, he has lost his magic, his talent, and his assurance. His wife has gone, his audience has left him, his agent can't persuade him to make a comeback. Consumed by an erotic desire, he plunges into a darker and more shocking end.
Keywords: Actors -- Fiction; Psychological fiction; Fiktionale Darstellung